EU labour in agricultural sector of the United Kingdom - Katarina Barathova (ZBW – Leibniz Information Centre for Economics, 2018)
Today, many EU states face labour shortages in different sectors of economy, including agricultural sectors. Labour migration represents the solution which enables countries to cope with this problem. This is also the case of agricultural sector of the United Kingdom. After the EU enlargement, out of all old Member States only the United Kingdom alongside with Ireland and Sweden granted people from the Central and Eastern Europe countries free access to their labour markets. In case of the UK this was seen as strategic step, since the government recognized the important role of migrant workers in the growth of the UK's economy. Soon after enlargement, the UK became favourite destination of migrant workers from A-8 countries. In 2007, when another two countries – Bulgaria and Romania joined the EU, the economic situation was different and the UK decided to apply transitional arrangements. Despite this, there were a lot of migrants coming to the UK and most of them were working in agriculture, since for seasonal agricultural workers there was an exception. After the restrictions were removed in January, 2014, migration inflows from Bulgaria and Romania almost doubled. Before referendum in 2016, migration was an important issue and one of the main arguments of Leave campaign. Using available statistical data, the paper examines migration flows to the UK and describes key features of migration from EU with special focus on A-10 countries. The main objective is to evaluate the importance of migrant workers from these new Member States in the agriculture and food manufacturing industry of the UK and reveal possible implications associated with Brexit.
Keywords: J61; F22; Q10; 330; agriculture; migration; labour; horticulture; EU workers